THE INFLUENCE OF MARKETING AUDIT IN THE SUSTAINABLE OF COSTUMER LOYALTY - KHOSHAVY, DILMAN; SHARAFANY, RAMADAN (Journal of Duhok University, 2019)
The importance of research has been addressed from its variable’s importance, which is a relatively recent topics in the field of marketing specifically, and in theory the research is a modest contribution to the enrichment of literature relating to both marketing audit and sustainability of customer loyalty, but in practice is an attempt to identify the impact of marketing review in sustainability of customer loyalty in the field. The study aims to identify the nature of the correlation between the marketing audit and the sustainability of customer loyalty by studying the opinions of a sample of the managers of a number of telecommunications companies in the city of Duhok. The survey questionnaire was developed and used as a main tool for collecting data from the surveyed individuals, which reached (34) individuals. Using several statistical methods, the research hypotheses were tested. One of the most important conclusions was that "the marketing review has a positive and direct impact on the sustainability of the customer loyalty to the telecom companies in Duhok." The research also concluded a number of suggestions that the researcher considers suitable, In the process of marketing review and the submission of regular periodic reports in addition to reports to be submitted in exceptional circumstances.